Mengontruksi Kontrol Optimal Berkendala Pada Sistem LTI Dengan Keadaan Berkendala Menggunakan Metode Fungsi Penalti - Nurweni Putri; Iswan Rina (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
The optimal control problem is defined as a problem in determining the control u(t) that depends on time t, such that it produces the optimum value for the objective function. The optimal control system with constrained conditions can be changed to an optimal control system without constraints by constructing the value of u(t) so that u(t) is not constrained. In this research, we will examine how to determine an optimal control of a system of time-independent state space or Linear Time Invariant (LTI) with constrained states and minimize a given objective function. In addition, how to construct an optimal controller that is constrained to become an optimal controller without constraints using the penalty function method and its implementation using Matlab. The results of this study are that the optimal control is:.